Creation of Heterosis Hybrids of Cucumis Melo L. for the Protected Soil of Uzbekistan - Lyan Ekaterina. (Genius Journals, 2022)
For the first time in the republic, varieties of hothouse melons were created, which are distinguished by high yield, high palatability, resistance to major diseases common in protected ground. The hybrid F1 Zarkhal was submitted to the variety testing inspection, and the promising hybrids F1 L-160 × L-179 and F1 L-161 × L-179 are undergoing production tests in greenhouses of the republic
Keywords: Melon; variety samples; hybrids; sowing